What Job Attributes are Most Important for Job Seekers? Hint: Compensation and Benefits—What to do With This Knowledge and How to Signal to Job Seekers - Newman, Sean A.; Kinchak, Pavel; Gopalkrishnan, Shalini (Compensation and benefits review, 2025)
The job market in many sectors remains tricky. Major events like COVID, inflation, and a large demographic shift of who is participating in the workforce has made it difficult for organizations to attract the talent needed to be successful. The job attributes and programs that organizations are using to attract employees do not seem to be working as well today as in the past. Prior academic research noted that job and cultural fit were the most important characteristics for those seeking jobs; however, little new research has been published on this topic since 2020 and COVID. Through conjoint analysis, this quantitative research study of 300 prospective job applicants examines how job applicants consider and prioritize observable job and recruitment attributes in their evaluation of job opportunities. In this study, we found that compensation and workplace flexibility are the most important attributes that organizations can signal as they work to attract talent, which is a major shift from prior studies. Based on these findings, we offer several practical ideas for how compensation and benefits leaders can strategically use this data to align programs to what those in the job market seek.